Association of TNF-857C>T, TNFRSF1A36A>G, and TNFRSF1B676T>G Polymorphisms with Ischemic Stroke in a Greek Population - Sofia Markoula; Anthoula Chatzikyriakidou; Sotirios Giannopoulos; Kargiotis Odysseas; Sofia Markou; Konstantinos Vemmos; Ioannis Georgiou; Athanassios P. Kyritsis (Stroke Research and Treatment)
Background. The role of genetic factors in the predisposition to develop ischemic stroke has been assessed by previous studies. The main goal of the current study was to determine any possible role of TNF-857C>T,TNFRSF1A36A>G, and TNFRSF1B676T>G polymorphisms in risk for stroke. Materials and Methods. One hundred seventy-three patients with first ever ischemic stroke of solely atherosclerotic etiology in Northwest Greece and a control group of 179 healthy unrelated subjects were evaluated. Results. TNFα-857TT, TNFR136AA, and TNFR2676TT genotypes were significantly increased in the patient group compared to controls (𝑃=.008, OR = 2.47 (1.26–4.84), 𝑃=.005, OR = 1.97 (1.22–3.17), and 𝑃=.003, OR = 2.2 (1.43–3.37), resp.). In addition, the TNFR136A and the TNFR2676T alleles were found significantly increased in patients compared to controls (𝑃=.009, OR = 1.48 (1.1–2) and 𝑃=.001, OR = 1.75 (1.25–2.46), resp.). Conclusion. The high incidence of these genotypes and alleles in patient group suggests that they are potentially predisposing factors for stroke in the Greek population studied. Large-scale multicenter controlled studies are needed to verify these polymorphisms effects on stroke susceptibility.